Metabolic functions of Pseudomonas fluorescens strains from Populus deltoides depend on rhizosphere or endosphere isolation compartment - Timm, Collin M.; Campbell, Alisha G.; Utturkar, Sagar M.; Jun, Se-Ran; Parales, Rebecca E.; Tan, Watumesa A.; Robeson, Michael S.; Lu, Tse-Yuan S.; Jawdy, Sara; Brown, Steven D.; Ussery, David W.; Schadt, Christopher W.; et al. (Frontiers in Microbiology, 2015)
The bacterial microbiota of plants is diverse, with 1,000s of operational taxonomic units (OTUs) associated with any individual plant. In this work we investigate the differences between 19 sequenced Pseudomonas fluorescens strains, isolated from Populus deltoides rhizosphere and endosphere and which represent a single OTU, using phenotypic analysis, comparative genomics, and metabolic models. While no traits were exclusive to either endosphere or rhizosphere P. fluorescens isolates, multiple pathways relevant for plant-bacterial interactions are enriched in endosphere isolate genomes. Further, growth phenotypes such as phosphate solubilization, protease activity, denitrification and root growth promotion are biased towards endosphere isolates. Endosphere isolates have significantly more metabolic pathways for plant signaling compounds and an increased metabolic range that includes utilization of energy rich nucleotides and sugars, consistent with endosphere colonization. Rhizosphere P. fluorescens have fewer pathways representative of plant-bacterial interactions but show metabolic bias towards chemical substrates often found in root exudates. This work reveals the diverse functions that may contribute to colonization of the endosphere by bacteria and are enriched among closely related isolates.